Isolation of Antagonistic Endophytes from Banana Roots against Meloidogyne javanica and Their Effects on Soil Nematode Community - Su, Lanxi; Shen, Zongzhuan; Ruan, Yunze; Tao, Chengyuan; Chao, Yifan; Li, Rong; Shen, Qirong (Frontiers in Microbiology, 2017)
Banana production is seriously hindered by Meloidogyne spp. all over the world. Endophytes are ideal candidates compared to pesticides as an environmentally benign agent. In the present study, endophytes isolated from banana roots infected by Meloidogyne spp. with different disease levels were tested in vitro, and in sterile and nature banana monoculture soils against Meloidogyne javanica. The proportion of antagonistic endophytes were higher in the roots of middle and high disease levels. Among those, bacteria were dominant, and Pseudomonas spp., Bacillus spp. and Streptomyces spp. showed more abundant populations. One strain, named as SA, with definite root inner-colonization ability was isolated and identified as Streptomyces sp. This strain showed an inhibiting rate of > 50% in vitro and biocontrol efficiency of 70.7% in sterile soil against Meloidogyne javanica, compared to the control. Greenhouse experiment results showed that the strain SA exhibits excellent biological control ability for plant-parasites both in roots and root-knot nematode infested soil. SA treatment showed a higher number of bacterivores, especially for Mesorhabditis and Cephalobus. The maturity index (MI) was significantly lower, while enrichment index (EI) was significantly higher in the SA treatment. In conclusion, this study presents an important potential application of the endophytic strain Streptomyces sp. for the control of plant-parasitic nematodes, especially Meloidogyne javanica, and presents the effects on the associated variation of the nematode community.